Cross-sectional analysis of Piroplasma species-infecting camel (Camelus dromedaries) in Egypt using a multipronged molecular diagnostic approach - Mahdy, Olfat A.; Nassar, Ahmed M.; Elsawy, Bassma S. M.; Alzan, Heba F.; Kandil, Omnia M.; Mahmoud, Mona S.; Suarez, Carlos E. (Frontiers in Veterinary Science, 2023)
Camel piroplasmosis is a tick-borne disease (TBD) caused by hemoprotozoan parasites. Hereby, we describe a cross-sectional study aiming at identifying Piroplasma spp. infecting camels in Egypt using a multipronged molecular diagnostic approach. A total of 531 camel (Camelus dromedarius) blood samples were collected from slaughterhouses at different governorates in Egypt for analysis during the period from June 2018 to May 2019. Piroplasma spp. were identified using microscopical examination and several different and sequential polymerase chain reaction (PCR) assays targeting the 18S rRNA genes. Microscopical and molecular prevalence overall in the samples were 11% (58/531) and 38% (203/531), respectively. Further discriminative multiplex PCR analysis targeting the 18S rRNA gene applied on all piroplasma spp. positive samples allowed the detection of T. equi (41%), B. caballi (5.4%), B. bigemina (0.5%) and B. bovis (4%). Additionally, Blast analysis of nested (n) PCR, targeting V4 region, amplicon sequences resulted in the identification of B. vulpes (22%), Babesia sp. (9%), and Theileria sp. (3%). Overall, the results of this study confirmed high prevalence of TBDs caused by several types of piroplasm hemoparasites in camel and suggests the need for future interventions aimed at improving the control of these potentially debilitating diseases that may be threatening important economic resources and food security in Egypt.